ANALYSIS OF FARMERS’ RISK PREFERENCES IN RICE FARMING INSURANCE PROGRAM IN SRAGEN REGENCY - Dzulfriansyah, Mochammad Immam; Roessali, Wiludjeng; Kariyasa, I Ketut (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Rice farming is closely related to climate and weather in the business process, especially the on-farm process in the crop area. Climate risk in rice farming is closely related to the occurrence of floods, droughts, and attacks of Plant Disturbing Organisms (OPT). Therefore, it is necessary to overcome uncertainty to protect farmers and their farms, namely agricultural insurance. Agricultural insurance shows partiality to farmers to anticipate the risk of farming losses. Sragen Regency is one of the rice production centers in Central Java Province, so its farms need to be protected from risks through Rice Farming Insurance (AUTP). The purpose of this study is to analyze farmers' behavior in conducting rice farming through their risk preferences in Sragen Regency. The research was conducted using the survey method. Data were collected by interview technique using questionnaires. The number of samples taken from 100 rice farmers in Sragen Regency from three representative Sub-districts with specific criteria, namely Tanon Sub-district, Sidoharjo Sub-district, and Sambirejo Sub-district. The population in this study are rice farmers who participated in the Rice Farming Insurance (AUTP) program from 2018 to 2020. Data analysis uses the Multiple Price List (MPL) approach. Some previous studies analysing farmers' willingness to pay premiums in the AUTP programme have not included farmers' risk preference factors in the analysis. In addition, there is no research that discusses farmers' willingness to pay for AUTP premiums in Sragen Regency. Therefore, this research is expected to be a literature study in formulating strategies related to the implementation of the AUTP programme in the future by considering farmers' risk preferences, especially in Sragen Regency. The results showed that rice farmers in Sragen Regency have a very risk-averse risk preference, which means that they are risk-averse individuals when farming. Therefore, the Rice Farming Insurance (AUTP) program can be utilized by farmers as a form of risk mitigation implementation in their farming operations.